Peningkatan Prestasi Belajar Bahasa Indonesia Melalui Media Audio Visual - Imam Buchori (Universitas Mathla'ul Anwar Banten, 2021)
This study aims to determine an increase in Indonesian language learning achievement through Audio Visual media for class IX students of SMP Negeri 10 Cibeber. This study uses audio-visual media in learning Indonesian and is carried out in three cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The results showed that the lowest score in the first cycle was 62, the highest was 80, the average was 65, the number of students who had completed was 20 and those who had not, were 14 students. In the second cycle, the lowest score was 65, the highest was 87, the average was 73, 28 students who completed and 6 students who had not. In cycle III, the lowest score was 75, the highest was 95, the average was 82, all students completed. These results indicate that learning with the strategy of using audio-visual media is very influential on student learning achievement, therefore it should be developed and implemented in the Indonesian language learning process so that aspects of language learning can be applied in an integrated manner.